2014
DOI: 10.1007/s40653-014-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Coping Styles in an Adolescent Trauma Sample

Abstract: Individuals generally use the same coping styles across situations. It is important to identify maladaptive coping in adolescents as coping patterns may persist into adulthood, and are associated with mental health. The present study used a cross-sectional design to investigate the combined effect of personality traits, attachment, locus of control, and social support on rational (problem-focused), avoidant, and emotion-focused coping in 320 trauma-exposed adolescents. The combined variables only explained 20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…There is mounting evidence that exposure to trauma in childhood is associated with the coping strategies and skills youth employ to respond to these experiences (Bal et al 2009; Braun-Lewensohn et al 2009; Christiansen et al 2014); yet it is unclear whether there are lasting effects of trauma on the patterns of coping behaviors youth continue to use. With exposure to trauma affecting around 40% of U. S. children under 13 years of age (Koenen et al 2010), and the knowledge that these experiences can have long-term consequences for cognition, neural development, and behavior (Danese and Baldwin 2017), it is critical to understand the mechanisms through which traumatic events influence and shape later coping responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that exposure to trauma in childhood is associated with the coping strategies and skills youth employ to respond to these experiences (Bal et al 2009; Braun-Lewensohn et al 2009; Christiansen et al 2014); yet it is unclear whether there are lasting effects of trauma on the patterns of coping behaviors youth continue to use. With exposure to trauma affecting around 40% of U. S. children under 13 years of age (Koenen et al 2010), and the knowledge that these experiences can have long-term consequences for cognition, neural development, and behavior (Danese and Baldwin 2017), it is critical to understand the mechanisms through which traumatic events influence and shape later coping responses.…”
Section: Discussionmentioning
confidence: 99%
“…These avoidant coping behaviors have been shown to mediate the association between trauma and subsequent symptoms (e.g., post-traumatic stress, fear, anger, depression; Bal et al 2003). Further, the use of negative emotion-focused coping is associated with a history of multiple exposures to trauma and correlates with higher rates of PTSD symptoms, with avoidant and emotion-focused coping behaviors accounting for 25% of the variance in those symptoms (Christiansen et al 2014). However, problem-focused coping has been less well studied, and extant research has produced mixed findings.…”
Section: The Effects Of Trauma On Coping Behaviorsmentioning
confidence: 99%
“…Studies that have found emotion-focused coping to be adaptive in females have generally used unconfounded coping measures. Thus, it is possible that the positive association between emotion-focused coping and PTSD severity in mothers in the present study is due to a confounding of emotion-focused coping with distress [25,40,43] and may thus reflect a moderation effect of sex on the relationship between negative affectivity/distress and PTSD, rather than between emotion-focused coping and PTSD. However, one study has reported that certain types of emotion-focused coping appear to be maladaptive in females only [23].…”
Section: Variablementioning
confidence: 92%
“…Negative affectivity or neuroticism is related to coping efforts in general because it is associated with a heightened experience of distress and threat [56] and therefore am increased need for coping [57] However, because neurotic persons are easily overwhelmed by stress, they are very likely to seek to avoid stressors and decrease discomfort. Strong positive associations between negative affectivity/neuroticism and emotional coping and less strong but still significant to rational coping is found in other studies [58] [59].…”
Section: Psychological Factors and Copingmentioning
confidence: 51%
“…It is often consider a consequence of PTSD and to be associated with high levels of dissociation [60]. In a recent study [58], PTSD severity failed to predict somatization after negative affectivity was controlled for. The authors suggested that one possibility is that negative affectivity mediates the effect of PTSD on somatization.…”
Section: Psychological Factors and Copingmentioning
confidence: 99%